2016
DOI: 10.18632/oncotarget.11303
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the T790M mutation of EGFR in plasma of advanced non-small cell lung cancer patients with acquired resistance to tyrosine kinase inhibitors (West Japan oncology group 8014LTR study)

Abstract: IntroductionNext-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) have been developed to overcome resistance to earlier generations of such drugs mediated by a secondary T790M mutation of EGFR, but the performance of a second tumor biopsy to assess T790M mutation status can be problematic.MethodsWe developed and evaluated liquid biopsy assays for detection of TKI-sensitizing and T790M mutations of EGFR by droplet digital PCR (ddPCR) in EGFR mutation–positive non–small cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 16 publications
4
44
3
Order By: Relevance
“…Interestingly, 18/164 patients with plasma T790M-positive genotyping were T790M-negative on tissue analysis, showing favorable clinical outcomes similar to those of patients with T790M-positive tumor tissue (Oxnard et al, 2016). These data, consistently with those observed in other studies evaluating plasma genotyping approach at the time of PD (Takahama et al, 2016;Thress et al, 2015), demonstrated a lower specificity of plasma-based detection of T790M at PD compared to EGFR-activating mutations detection at baseline, likely due to the higher heterogeneity of TKI-resistant tumors. As single tissue biopsy is just a snapshot of the tumor not reflecting its spatial heterogeneity, ctDNA could be more representative of the overall tumor mutation status, allowing to identify different targetable alterations driving tumor resistance.…”
Section: Potential Application At Progressionsupporting
confidence: 84%
“…Interestingly, 18/164 patients with plasma T790M-positive genotyping were T790M-negative on tissue analysis, showing favorable clinical outcomes similar to those of patients with T790M-positive tumor tissue (Oxnard et al, 2016). These data, consistently with those observed in other studies evaluating plasma genotyping approach at the time of PD (Takahama et al, 2016;Thress et al, 2015), demonstrated a lower specificity of plasma-based detection of T790M at PD compared to EGFR-activating mutations detection at baseline, likely due to the higher heterogeneity of TKI-resistant tumors. As single tissue biopsy is just a snapshot of the tumor not reflecting its spatial heterogeneity, ctDNA could be more representative of the overall tumor mutation status, allowing to identify different targetable alterations driving tumor resistance.…”
Section: Potential Application At Progressionsupporting
confidence: 84%
“…Revolutionaly advancement of this non-invasive procedure would raise the convenience and feasibility of rebiopsy. Indeed, liquid biopsy using digital PCR has demonstrated its effectiveness to detect T790M mutation after acquired resistance to EGFR-TKIs (22). Liquid biopsy would compensate for the disadvantages of histological rebiopsy in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, absence of brain metastasis has been shown to be associated with prolonged OS in treatment with EGFR-TKIs (17). Recently, a non-invasive approach to the detection of gene mutations using cell-free DNA extracted from the plasma has been developed (18). Novel methods for detecting gene mutations that develop during treatment with EGFR-TKIs are an important aspect of the optimization of personalized therapy.…”
mentioning
confidence: 99%